The Binding of PD-L1 and Akt Facilitates Glioma Cell Invasion Upon Starvation via Akt/Autophagy/F-Actin Signaling - Chen, Ruo Qiao; Xu, Xiao Hong; Liu, Feng; Li, Chun Yang; Li, Yuan Jun; Li, Xiang Rui; Jiang, Guo Yong; Hu, Feng; Liu, Di; Pan, Feng; Qiu, Xin Yao; Chen, Xiao Qian (Frontiers in Oncology, 2019)
Glioma, especially glioblastoma, is pathologically characterized by high aggressiveness, which largely contributed to the ineffectiveness of current therapies. It has been recently reported that intrinsic PD-L1 can regulate tumor malignancy, whereas underlying mechanisms remain mostly unclear. Here, we report a novel mechanism by which PD-L1 promotes glioma cell infiltration. In orthotopic glioma models, PD-L1 expression was up-regulated predominantly in glioma cells in the infiltrating front. For PD-L1-overexpressed glioma cells, PI3K/Akt and actin regulations were among the top six most altered signaling pathways as detected by RNA-sequencing. PD-L1 significantly activated Akt/F-actin signaling while suppressed autophagic signaling upon cell starvation. Mechanistically, PD-L1 preferentially bound to Akt among various PI3K/Akt signaling proteins. Serial truncation identified the interaction between the 128-237aa fragment of PD-L1 and the 112-480aa fragment of Akt, which facilitates the membrane translocation/activation of Akt, and was unaffected by Perifosin (specific p-Akt inhibitor targeting Akt PH-domain). Taken together, our data indicate that in glioma cells, PD-L1 is induced to prevent autophagic cytoskeleton collapse via Akt binding/activation, facilitating glioma cell invasion upon starvation stress.